Cost of Care Saving of Terminal Cancer Adult Patient UsingPalliative Care Consultation in Cipto Mangunkusumo Hospital - Putranto, Rudi; Trisnantoro, Laksono; Hendra, Yos (UI Scholars Hub, 2017)
Introduction. Terminal cancer patients was increasing in Indonesia, and need attention to approach palliative and end of life care. Terminal cancer management was burden the hospital, because it causes high costly and the length of stay This study aimed to get a general picture of service palliative at Cipto Mangunkusumo, then to evaluate the relationship hospitalization and rates of inpatient services people with terminal cancer adults who received the intervention palliative care and to evaluate the relationship variable rates for accommodation (room), doctor visit, procedure/surgery, medicines and consumables, laboratory and radiology to palliative interventions in patients with terminal cancer in inpatient Dr. Cipto Mangunkusumo Hospital. Methods. This research was descriptive study with case control design and performed in the inpatient unit, Dr Cipto Mangunkusumo Hospital, during the month of January to December 2015. The subjects were medical records and billing of terminal cancer patients were .hospitalized adults in class III in January - December 2015 with National Health Insurance (BPJS). Inclusion criteria are terminal cancer patients, beusia ≥ 18 years, received palliative care consultation team while exclusion criteria are patients receiving palliative consultation on treatment days ≥ 25 days. Results. It is known that there is a significant relationship between palliative interventions to patients with hospital rates (p= 0.041), whereas there was no significant relationship between palliative interventions by the length of stay (p = 0.873). There is a significant relationship between palliative interventions and expenditures room rates, visite, action and medicine and palliative interventions. Conclusions. There is a significant relationship between palliative interventions with hospital rates. There is a significant relationship between palliative interventions and expenditures room rates, visite, action and medicine and palliative interventions. These data showed that palliative care intervention was saving money for hospital.